Combination of molecular networking and LC-MS/MS profiling in investigating the interrelationships between the antioxidant and antimicrobial properties of Curculigo latifolia - Mad Nasir, Nadiah; Ezam Shah, Nur Syafiqah; Zainal, Nurul Zulaikha; Kassim, Nur Kartinee; Mohd Faudzi, Siti Munirah; Hasan, Hanan (Multidisciplinary Digital Publishing Institute, 2021)
Curculigo is a potent plant with a variety of traditional uses, such as anti-oxidant, anti-diabetic, anti-tumor, anti-bacterial, anti-cancer, anti-osteoporosis, and wound-healing. The comprehensive profiling of the Curculigolatifolia metabolome was carried out by generating a molecular network (MN) from Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS) data to profile the methanol extract and correlating them with their antioxidant (2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH), total phenolic contents (TPC), and β-carotene) and antimicrobial (disk-diffusion agar method, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC)) properties. The antioxidant capacity was observed to be significantly higher in the rhizome crude extract, with 18.10 ± 0.91 µg/mL DPPH activity, and a β-carotene bleaching result of 35.20%. For the antimicrobial activity, the leaf crude extract exhibited a strong Staphylococcus aureus and Salmonella choleraesuis (8–15 ± 3.0 mm) inhibition in the disk-diffusion agar. The leaf extract also exhibited maximum antibacterial activity against S. aureus (MIC = ±0.25 mg/mL, MBC = ±0.25 mg/mL) and S. choleraesuis (MIC = ±0.25 mg/mL, MBC = ±0.25 mg/mL). LC-MS/MS analysis and MN revealed norlignans and phenolic glycosides as major metabolites in the rhizome and leaf extracts of the negative mode (M − H)−. Fourteen known compounds were identified, and three unknown compounds were putatively identified in the rhizome extract, while ten known compounds and six unknown compounds were putatively identified in the leaf extract.